Netnografia del dono. La socialità ai tempi di Facebook - Cirrone, Rossella (Antropologia Pubblica, 2024)
According to anthropological studies “all the paths of the gift lead back to Mauss” (Aria 2016), echoing back the key role of gift in traditional societies studies. In this vein, this research employs an original approach to update the definitions of good, consumption and gift, analysing this triad on a field yet unexplored: the digital space. By building on the study of Kula’s gifts exchange as a formal practice of social recognition (Mauss 1950), I have sought to apply this theoretical framework onto the case of Facebook. Within this specific cyber space, I have argued, the exchange of likes functions as a circulation of cyber-gifts which is aimed, on the one hand, at forming up social alliances between users and, on the other hand, at increasing the digital social capital of each user (Bourdieu 1979; Magaudda 2015). The methodological framework I have applied is the so-called netnography, which combines classic methods of ethnographic research with the purposes of social network research (Kozinets 2010). Lastly, I have proposed an anthropology of social practices in the cyber-space, revealing a capitalism of storytelling which meets the contemporary need for community (Bauman 2001).